Biorational Management of Post-harvest Sour Rot of Kinnow Fruits - Sharma, R. N. (International Journal of Economic Plants, 2026)
The experiment was conducted during the year 2007 at the Agricultural Research Station, Sriganganagar (Raj.). Kinnow (Citrus deliciosa) fruits were prone to attack by several microorganisms during storage and marketing. Sour rot caused by Geotrichum candidum Link. was one of the most prominent post-harvest rots of Kinnow fruits. Twelve native and exotic strains of fungal [Trichoderma hamatum (HP-20), T. harzianum (TG-1), T. viride-1, T. viride-2, Gliocladium deliquescens, G. virens, and Chaetomium globosum (HP-29)], yeasts [Debaryomyces hansenii, Sporidiobolus pararoseus (KFY-1)], and bacterial [Bacillus subtilis, Pseudomonas fluorescens (CHAO), P. fluorescens (Pf-1)] antagonists were evaluated against the G. candidum. Debaryomyces hansenii and S. pararoseus (KFY-1) proved superior over the rest of the antagonists tested against the pathogen by inhibiting 91.67 and 87.22% mycelial growth, respectively. Pseudomonas fluorescens (Pf-1), B. subtilis, and P. fluorescens (CHAO) exhibited 77.04, 69.07, and 66.67% growth inhibition, respectively. Maximum reduction in rot incidence was observed in fruits treated with spore suspension (109 cfu ml-1) of D. hansenii and S. pararoseus (KFY-1), where 88.30 and 84.11% in pre-inoculation and 85.32 and 78.79% in post-inoculation treatment were noted, respectively. Spore suspension (109 cfu ml-1) of P. fluorescens (Pf-1) and B. subtilis was found to be the next in order of bioefficacy against the fruit rotting, protected the treated fruits to the extent of 79.94, 77.15 and 74.18, 69.84%, respectively, in pre- and post-inoculation treatments.